The Effect of Product Quality, Brand Image, and Price Perception on Purchasing Decisions - Erika Ramadiana; Salman Paludi (Panorama Nusantara, 2022)
This study aims to determine whether there is an influence between Product Quality, Brand Image, and Price Perception on Purchase Decisions at H&M Kelapa Gading. The population is H&M customers who have bought H&M products at H&M Kelapa Gading store. This study used non-probability sampling with the method of accidental sampling as many as 100 respondents for sampling technique. Methods of collecting data using a questionnaire and measured by 5 options Likert Scale which has been tested for validity and reliability test. Meanwhile, for the data analysis method using multiple linear regression analysis with IBM SPSS software, followed by correlation coefficient analysis and coefficient determination analysis. From this study, it was found that product quality has no significant effect on purchasing decisions, brand image does not significantly affect purchasing decisions, and price perceptions have a positive and significant effect on purchasing decisions. Taken together, product quality, brand image, and price perception have a positive and significant effect on purchasing decisions.